Analisis Hubungan Biaya Pengembangan Dengan Laba Bersih di PT Industri Telekomunikasi Indonesia - Kosasih (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
The purpose of this research was to obtain the empirical evidence on the correlation of development costs on net income at PT Telekomunikasi Indonesia Indonesia. The research methods used in this research is descriptive and verification method with a quantitative approach. The data used are secondary data from financial statements from 2010-2016 obtained through annual financial reports, observation, internet browsing, library studies, and interviews. The results showed that there is correlation between development costs on net income at PT Telekomunikasi Indonesia Indonesia. The correlation between development costs and net income has a negative relationship. This means when rising development costs then net income down, otherwise when development costs down then net income rises, so the research hypothesis is accepted.